Conversations of Socrates - Xenophon (London, 1990)
After the execution of Socrates in 399 BC, a number of his followers wrote dialogues featuring him as the protagonist and, in so doing, transformed the great philosopher into a legendary figure. Xenophon's portrait is the only one other than Plato's to survive, and while it offers a very personal interpretation of Socratic thought, it also reveals much about the man and his philosophical views. In 'Socrates' Defence' Xenophon defends his mentor against charges of arrogance made at his trial, while the 'Memoirs of Socrates' also starts with an impassioned plea for the rehabilitation of a wronged reputation. Along with 'The Estate-Manager', a practical economic treatise, and 'The Dinner-Party', a sparkling exploration of love, Xenophon's dialogues offer fascinating insights into the Socratic world and into the intellectual atmosphere and daily life of ancient Greece.
Keywords: "Philosophy, Ancient"